Tinjauan Hukum Islam terhadap Tes DNA Sebagai Alat Bukti Tindak Pidana Pembunuhan - Hasna Afifah (Al Ahkam, 2020)
The rapid advancement of science and technology today, there are many new discoveries of the technology and that are conducive for evidentiary effort of a case conducted by a judge including voice recording technology, image recording, fingerprint tracing and DNA testing. With the charateristic of DNA, is very potential to be used in tracing the origin of a person’s offspring. Related to that, if there is a criminal act with the origin of a person’s offspring, such as rape, forgery of guardians, forgery of heirs, etc. That is very usefull for evidentiary efforts in court. But the problem is, the evidence of a criminal act in the court is under the formal juridical area, so the validity of something that be used as an evidence depends on the formal provisions governing it. Based on existing sources, it seems that an ordinary and in depth study of the discovery of DNA that connected with qarinah evidence in Islamic judicial procedure law has not been found, and if there is only a general discussion about al-qara’in (clues / indicators) that so far the information is not sufficient. In the middle of the scarcity, this is very interesting research to discuss as a reference that support the creation of justice. The study of DNA related wth the qarinah evidence needs to be carried out as a new scince, especially in the study of Islamic Law about position and strength of the DNA test as an evidence in the criminal act especially murder.